Faktor Faktor Risiko Stress Meningkatkan Kejadian Premenstrual Syndrome (PMS) pada Mahasiswa Kebidanan Poltekkes Kemenkes Banjarmasin - Nur Rohmah Prihatanti; Januarsih Januarsih; Megawati Megawati; Norlaila Sofia (JURNAL KEBIDANAN BESTARI, 2022)
Premenstrual Syndrome (PMS) is a collection of moderate to severe affective and physical symptoms that develop during the luteal phase of the menstrual cycle and disappear within a few days of menstruation. Complaints of Premenstrual Syndrome (PMS) that often occur are anxiety, fatigue, difficulty concentrating, difficulty sleeping, loss of energy, headache, abdominal pain, and breast pain. The prevalence of Premenstrual Syndrome (PMS) reaches 90% of the entire population of women of childbearing age in the world. In Indonesia, it reaches 85% experienced by women of childbearing age. As many as 20-50% of them experience severe Premenstrual Syndrome (PMS) symptoms that interfere with daily activities. The incidence of Premenstrual Syndrome (PMS) can increase because it is influenced by several risk factors, one of which is stress. The study used an analytical observational research design with a cross sectional approach. The research was conducted at the Midwifery Department of the Health Poltekkes of the Ministry of Health Banjarmasin and carried out in August-December 2021 with a population of all third semester students of the three diploma study program majoring in midwifery Poltekkes Ministry of Health Banjarmasin for the 2021/2022 academic year, which is as many as 40 people. Sample selection using simple random sampling method. Samples were taken randomly from the third semester student population of the three diploma study program majoring in midwifery for the 2021/2022 academic year with the requirement that they have experienced menstruation. The sample was calculated using the Slovin formula and the number of samples was 35 people. The independent variable is stress with the research instrument in the form of a questionnaire and the dependent variable is Premenstrual Syndrome (PMS) with the research instrument in the form of a questionnaire The Shortened Premenstrual Assessment Form (SPAF). From the results of a simple linear regression test, the results of the calculation of p-value = 0.000 or the value of Sig. 0.000 < 0.05, which means that stress increases the incidence of Premenstrual Syndrome (PMS) in students of the Department of Midwifery, Poltekkes Kemenkes Banjarmasin. Keyword: Students, Premenstrual Syndrome (PMS), Stress